Anomalous metamagnetic-like transition in a FeRh/Fe3Pt interface occurring at T approximate to 120 K in the field-cooled-cooling curves for low magnetic fields - Salem-Sugui, S.; Alvarenga, A. D.; Noce, R. D. [UNESP]; Guimaraes, R. B.; Salazar Mejia, C.; Salim, H.; Gandra, F. G. (American Institute of Physics (AIP), 2012)
We report on the magnetic properties of a special configuration of a FeRh thin film. An anomalous behavior on the magnetisation vs. temperature was observed when low magnetic fields are applied in the plane of a thin layer of FeRh deposited on ordered Fe3Pt. The anomalous effect resembles a metamagnetic transition and occur only in the field-cooled-cooling magnetisation curve at temperatures near 120 K in samples without any heat treatment. Copyright 2012 Author(s). This article is distributed under a Creative Commons Attribution 3.0 Unported License. [http://dx.doi.org/10.1063/1.4754154]